ASME 2012 Summer Bioengineering Conference, Parts a and B 2012
DOI: 10.1115/sbc2012-80206
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Multilayer Nanoshells With Hydrophobic Nanodomains for Delivery of Paclitaxel

Abstract: Efficient and effective delivery of poorly water-soluble drug molecules, which constitute a large part of commercially available drugs, is a major challenge in the field of drug delivery. Several drugs including paclitaxel (PTX) which are used for cancer treatment are hydrophobic, exhibit poor aqueous solubility and need to be delivered using an appropriate carrier. In the present work, we engineered Taxol-loaded polyelectrolyte films and microcapsules by pre-complexing PTX with chemically modified derivative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Effective drug delivery vectors have several key requirements [240][241][242][243][244]: low toxicity and optional degradability; high loading capacity; triggered release mechanisms, such as pH-, enzyme-, or redox-triggered; low immunogenicity; and targeting groups to direct the vector to designated sites. Drug and therapeutic molecule loading can be achieved by several routes, including: co-assembly of polymer-drug conjugates [119,151,245]; drug post-loading by temporarily altering capsule permeability [246][247][248][249][250][251]; pre-loading of therapeutics to functional templates [176,[252][253][254][255][256][257]; or incorporation into specific domains of the capsule [142,258,259].…”
Section: Drug and Vaccine Deliverymentioning
confidence: 99%
“…Effective drug delivery vectors have several key requirements [240][241][242][243][244]: low toxicity and optional degradability; high loading capacity; triggered release mechanisms, such as pH-, enzyme-, or redox-triggered; low immunogenicity; and targeting groups to direct the vector to designated sites. Drug and therapeutic molecule loading can be achieved by several routes, including: co-assembly of polymer-drug conjugates [119,151,245]; drug post-loading by temporarily altering capsule permeability [246][247][248][249][250][251]; pre-loading of therapeutics to functional templates [176,[252][253][254][255][256][257]; or incorporation into specific domains of the capsule [142,258,259].…”
Section: Drug and Vaccine Deliverymentioning
confidence: 99%
“…There is tremendous potential to combine this pH‐based targeting with drug‐releasing LbL film architectures to deliver a chemotherapeutic at a tumor site. In fact, it has been shown that HA derivatives containing hydrophobic nanodomains can be complexed with hydrophobic small molecules, including the chemotherapeutic paclitaxel, to allow for drug loading into an LbL film containing these modified HA molecules and polyelectrolytes, including PLL and quaternized chitosan . The release of paclitaxel from these films was shown to be hyaluronidase‐sensitive, an enzyme that is often upregulated in certain breast cancers .…”
Section: Lbl Assembly For Cellular and Tissue Engineering Applicationsmentioning
confidence: 99%
“…In fact, it has been shown that HA derivatives containing hydrophobic nanodomains can be complexed with hydrophobic small molecules, including the chemotherapeutic paclitaxel, to allow for drug loading into an LbL film containing these modified HA molecules and polyelectrolytes, including PLL and quaternized chitosan . The release of paclitaxel from these films was shown to be hyaluronidase‐sensitive, an enzyme that is often upregulated in certain breast cancers . HA has also been used to capture paclitaxel‐loaded block copolymer micelle nanocarriers subsequently layered with polycations, leading to controlled release of paclitaxel and demonstrating reduced in vitro proliferation of human aortic smooth muscle cells …”
Section: Lbl Assembly For Cellular and Tissue Engineering Applicationsmentioning
confidence: 99%
“…Liver parenchymal cells have thus been successfully targeted by glycans-presenting LbL capsules, as these cells express receptors presenting lectins, proteins that recognize sugar complexes [101103] . Tumor-targeted systems have also been developed, targeting either folate receptors [104] or CD44 glycoproteins [105,106] , as these receptors are overexpressed on many cancer cell membranes.…”
Section: Introductionmentioning
confidence: 99%